An experimental study on water purification performance of modified volcanic rock ecological concrete - Fei Peng Liu; Jing Xu; Jian Xin Zhao; Li Feng Liu; Meng Ya Zhang; Shu Cheng Tan (Scientific Reports)
Abstract Eco-concrete is an engineered porous material, often used in pervious pavement and slope protection. Volcanic rock, due to its loose and porous structure, can absorb pollutants and improve the performance of eco-concrete. Here, this study determined the performance of eco-concrete modified with different contents of volcanic rock in sewage purification. The results showed that eco-concrete purified sewage, and that adding volcanic rock further improved the removal capacity of total nitrogen (TN), total phosphorus (TP), and chemical oxygen demand (COD) by 34.1, 47.3, and 6%, respectively. The water purification mechanism of volcanic rock eco-concrete (VREC) was mainly physical water absorption (mechanical retention) and microbial degradation. With the increase in the content of cement slurry, the adsorption amount decreased, porosity decreased, and strength increased, gradually not meeting the engineering application requirements. Therefore, the high porosity volcanic rock eco-concrete (VREC) had the best water purification performance. The result conclude that eco-concrete should be prepared with an admixture of volcanic rock with 30% porosity for the best sewage purification results.